N-Butanol Extract of Modified You-Gui-Yin Attenuates Osteoclastogenesis and Ameliorates Osteoporosis by Inhibiting RANKL-Mediated NF-κB Signaling - Zeng, Qinghe; Xu, Rui; Ling, Houfu; Zhao, Shan; Wang, Xu; Yuan, Wenhua; Gu, Mancang; Xu, Taotao; Wang, Pinger; Ruan, Hongfeng; Jin, Hongting; Qu, Hangbo; et al. (Frontiers in Endocrinology, 2022)
Postmenopausal Osteoporosis (PMOP) is the most prevalent primary osteoporosis, attributable to an imbalance in osteoblast and osteoclast activity. Modified You-Gui-Yin (MYGY), a traditional Chinese herbal formula, is able to effectively treat PMOP, while the critical components and pharmacological mechanisms of MYGY are still unclear. In this study, we aimed to investigate the therapeutic effects and underlying mechanisms of N-butanol extract of MYGY (MYGY-Nb) in ovariectomized (OVX)-induced osteoporosis mice. Histological staining and micro-computed tomography (μCT) analysis showed that MYGY-Nb was more effective in the suppression of OVX-induced bone loss than MYGY original formula. Subsequently, liquid chromatography and mass spectrometry analysis identified 16 critical compounds of MYGY-Nb and some of them are reported to affect osteoclast functions. Furthermore, in vivo and in vitro experiments demonstrated that MYGY-Nb significantly attenuated osteoclastogenesis by down-regulating RANKL-mediated NF-κB signaling. In conclusion, our study indicated that MYGY-Nb suppresses NF-κB signaling and osteoclast formation to mitigate bone loss in PMOP, implying that MYGY-Nb and its compounds are potential candidates for development of anti-PMOP drugs.